Effects of a multidisciplinary heart failure program in short term readmissions of heart failure patients, preliminary results. (25th November 2020) - Gorriz Magana, J; Espinosa Pascual, M.J; Abad Romero, R; Olsen Rodriguez, R; Nieto Ibanez, D; Perela Alvarez, C; Fraile Sanz, A; Saavedra Falero, J; Perea Egido, J
Abstract: Background: Unexpected readmissions are frequent among heart failure patients, due to their natural history that implies multiple readmissions, with high costs and clinical relevance. Purpose: We aimed to assess the impact of a Multidisciplinary Heart Failure Program (MHFP) on the readmission-free period after an episode of acute decompensated heart failure (ADHF). Methods: We carried out an analytical and observational study including all patients admitted to our Universitary Hospital, which covers 220, 000 individuals, with an episode of heart failure when there was not a Multidisciplinary Heart Failure Program (January 2013 to December 2013). Once the MHFP was established, we compared non-MHFP patients with every patient admitted during February 2019 and February 2020 in terms of clinical data, imaging technique findings and short-term readmissions. Results: The rate of readmission during this period was a 24.8% in non-MHFP and 17.2% in MHFP (p=0.15). However, we could find differences in median time to readmission due to ADHF, that was 1.74 months (CI 95%, 0.12–3.35) in non-MHFP, compared to 5.125 months (CI 95%, 4.15–6.09) in MHFP (p=0.002) (see Graph 1). There were also no significant differences in terms of basic characteristics between the MHFP and the non-MHFP patients (age, gender, left ventricular ejection fraction, left bundle branch block, hypertension). It is remarkable that establishing a MHFP has lengthened the readmission-free period. The rate of decompensation in the first and sixth month was respectively in the non–MHFP 9% and 21%; and in the MHFP 2% and 10%. Conclusion: According to our results, the implantation of this Multidisciplinary Heart Failure Program has shown a reduction in the time to ADHF readmission compared with a cohort of similar pts some years before, which is clinically relevant. Funding Acknowledgement: Type of funding source: None